Immobilization of bovine serum albumin on chitosan/PVA film: Physical and mechanical properties investigation / Nurul Mujahidah Ahmad Khairuddin - Nurul Mujahidah , Ahmad Khairuddin (2019)
Chitosan/ polyvinyl alcohol (Ch/PVA) blended film was prepared by direct blend process and solution casting methods. In order to reduce the swelling ratio and enhance the chemical and mechanical stability, Ch/PVA film was crosslinked with glutaraldehyde in order to produce Ch-g-PVA. Bovine serum albumin (BSA) was used as a model protein to incorporate into the Ch-g-PVA. The chemical structure and morphological characteristics of films were studied by FT-IR and Field-emission scanning electron microscopy (FESEM). Mechanical and physical properties of blended films such as tensile properties in the dry and wet states, water uptake, and water contact angle measurement were characterized. Blending PVA and chitosan improved strength and flexibility of the films. Crosslinking with glutaraldehyde further improves the tensile strength and decrease the hydrophilicity of films. BSA immobilized on the Ch-g-PVA film was calculated as BSA encapsulation efficiency. All results indicated that chemical modification with glutaraldehyde and BSA turns films more hydrophobic